Phase behaviour and non-monotonic film drying kinetics of aluminium chlorohydrate-glycerol-water ternary solutions - Ferretti,GL; Cabral,JP (Journal of Colloid and Interface Science, 2016)
We study the drying and film formation of a model ternary system comprising an inorganic salt (aluminium chlorohydrate, ACH), a humectant (glycerol) and water. Employing viscometric, X-ray diffraction, calorimetric, dynamic vapour sorption, spectroscopic, gravimetric and adhesion measurements, we examine the roles of humectant concentration, temperature and relative humidity (RH) in the phase behaviour and kinetics of film formation. Equilibrium film compositions are found to be non-monotonic with glycerol content. Around 15:4 ACH:glycerol mass ratio, films exhibit enhanced, albeit slower, desiccation, with water content lower than that of binary ACH–water solutions. At higher glycerol content, drying is faster, yet the resulting films have higher water content and remain tackier. Water adsorption/desorption is shown to be fully reversible, and share a similar non-monotonic kinetic dependence on glycerol composition. These findings are rationalised in terms of the competitive binding of water and glycerol to ACH, the overall miscibility and glass formation within the ternary system. Our study is relevant to a range of salt formulations, employed in a variety of commercial applications, including lyoprotectants and personal care products.